Fabrication of iron loaded whey protein isolate/gum Arabic nanoparticles and its adsorption activity on oil-water interface. (June 2021) - Yao, Xiaolin; Xu, Kai; Shu, Meng; Liu, Ning; Li, Na; Chen, Xiaoyu; Nishinari, Katsuyoshi; Phillips, Glyn O.; Jiang, Fatang
Abstract: Design and fabrication of iron fortifier is very essential in the prevention or improvement of iron-deficiency anemia in food industry. In this study whey protein isolate (WPI) and gum arabic (GA) loaded with ferric ions was expected to be self-assembled to form stable nanoparticles by heating at 85 °C for 15 min at pH 4.0. It is illustrated that WPI/GAFe3+ nanoparticles were more uniformly dispersed in comparison with the easily aggregative GAFe3+ complex. The tightly binding of ferric ions was confirmed by FTIR and XPS. During formation of WPI/GAFe3+ aggregates induced by heating, the disulfide bond was formed and the surface hydrophobicity was significantly enhanced. The ferric ions release rate of WPI/GAFe3+ nanoparticles was significantly slower than that of GAFe3+ complex in simulated gastric juice due to the fact that the assembled structure exhibited a delayed effect on the hydrolysis of peptides catalyzed by pepsin during its internal diffusion into nanoparticles. WPI/GAFe3+ nanoparticles contributed to a good adsorption activity on oil-water interface between WPI and GAFe3+ complex because of its high steric hindrance. The decrease of interfacial tension with sequential adsorption demonstrated that WPI/GAFe3+ nanoparticles could be electrostatically adsorbed onto positively charged sodium caseinate interface, or co-adsorbed onto non-ionic Tween 80 interface, forming a more stable interface with higher steric hindrance and lower interfacial energy. Thus, the self-assembled WPI/GAFe3+ nanoparticles would have great potential in the application for iron fortification especially in food emulsion system. Graphical abstract: Schematic illustration for the formation of WPI/GAFe3+ nanoparticles. Image 1 Highlights: WPI and iron loaded GA could be self-assembled to form stable nanoparticles by heating at pH 4.0. WPI/GAFe3+ nanoparticles dispersed more uniformly compared with the aggregative GAFe3+ complex. Disulfide bond and surface hydrophobicity increased significantly along with the formation of WPI/GAFe3+ nanoparticles. WPI/GAFe3+ nanoparticles contributed to a good adsorption activity on oil-water interface.